Experiment of the Acaricidal Effects of the Clove, Syzygium aromaticum and Lemongrass, Cymbopogon citratus against Otodectes cynotis (ear mites) on the Stray Cat’s Ear - Ahmad Zaim Syirazi, Azni Raes (Universiti Malaysia Sarawak (UNIMAS), 2022)
This study is on the acaricidal effect of clove, Syzygium aromaticum and lemongrass, Cymbopogon citratus to control ear mites, Otodectes cynotis infestation on stray cats. Otodectes cynotis are most common of ectoparasites for cats and can be also found on dogs, rabbits and ferrets. It is most commonly found in the ear canal, but it can also survive on the skin's surface. Due to the tropical environment in Malaysia, the mites are easy to spread and reproduce. Thus, the objectives of this study were to compare the number of ear mites, O. cynotis in cats’ ears before and after using the clove and lemongrass solution and to determine the effectiveness of clove, S. aromaticum and lemongrass, C. citratus to kill ear mites in cats’ ears. In this experiment, a mixture of 80 g of clove and 80 g of lemongrass and 80 ml of virgin coconut oil were used by dropping the solution into the cat’s ear canal. The acaricidal effect of clove and lemongrass were effective against the ear mites due to reduce the number of O. cynotis in the cat’s ear before and after the treatment.